Factors Affecting Choice of Childbirth Place among Childbearing Age Women in Western Ethiopia: A Community-Based Cross-Sectional Study - Bekuma, Tariku Tesfaye; Firrisa, Belaynesh; Negero, Melese Girmaye; Kejela, Gemechu; Bikila, Haile (International Journal of Reproductive Medicine, 2020)
Background. Access to proper medical attention and hygienic conditions during delivery can reduce the risk of complications and infections that may lead to serious illness or death or for the mother, baby, or both. In Ethiopia, the high maternal mortality rate with delivery by unskilled birth attendants shows low utilization of maternal health services. Objective. This study was aimed at assessing factors determining the choice of childbirth place among women of childbearing age in Jimma Arjo District. Method. A cross-sectional design was conducted in Jimma Arjo District, East Wollega Zone, Ethiopia, from March 20 to April 20, 2018. Multistage sampling technique was used to select a total sample of 506 participants. Data were collected using structured questionnaires to interview women of childbearing age with two trained data collectors. Data was entered into Epi Info and exported to SPSS software version 20 for analysis. Data was checked for its completeness, cleaned, entered, and analyzed accordingly. Bivariate and multivariable data analyses were used to examine factors affecting choice of childbirth place. Results. A total of 506 women participated in this study, giving a response rate of 97.8%. The study investigated that home delivery was found to be 200 (39.5%)in the study area. Factors found to be statistically associated with choice of institutional delivery at p<0.05 were history of obstetric difficulties (AOR=6, 95%CI=2.08,17.60), woman educational status (AOR=4.4, 95%CI=1.47,13.42), husband educational status (AOR=4, 95%CI=1.43,11.60), two or more ANC visits (AOR=4, 95%CI=1.95,8.52), and accessibility to vehicle transportation (AOR=2.8, 95%CI=1.23,6.46). Conclusion. Preferring health facility as the birthplace in this study seems relatively better compared to other studies. It is shown that both mothers and their husbands attending secondary and greater educational level, history of obstetric difficulties, two or more ANC visits, and physical accessibility to health care facility have influenced mothers to prefer a health institution as the childbirth place. Therefore, any programs aimed at increasing the choice of institutional delivery should work on increasing ANC attendance and transportation facilities in the study area.